2006
DOI: 10.1007/s10517-006-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of changes in hepatic vessels after correction of experimental aortic coarctation

Abstract: Structural changes in hepatic vessels were studied in pups with experimental aortic coarctation and animals with corrected defect. Reconstruction of vessels was assayed by functional, morphometric, and histological methods. Aortic coarctation in pups was followed by a decrease in circumferential strain of the wall of hepatic arteries. These changes were accompanied by atrophy and sclerosis of the media. The arterial bed had a greater number of vessels with intimal muscles. Muscle bundles in large hepatic veins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, we found as many as sixteen different formulae to calculate WLR. Some studies employed the diameter or radius: WTh/ID,[50],[52],[53]; ED—ID/2ID[54]; ED/ID[55]; WTh/IR[11][16]; a media index WTh/IR with IR specifically defined as the distance from the center of the arterial lumen to the middle point of the media[56]; 2WTh/ED[57],[58]; 2WTh/ID[59]; WTh/ED[60]; or ID/ED[61]. Others have measured WLR from the perimeters as EP/IP[46],[47],[48], or used the area: MCSA/LCSA[14],[15],[49]; MCSA/TCSA[44]; LCSA/MCSA[43]; LCSA/TCSA[62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we found as many as sixteen different formulae to calculate WLR. Some studies employed the diameter or radius: WTh/ID,[50],[52],[53]; ED—ID/2ID[54]; ED/ID[55]; WTh/IR[11][16]; a media index WTh/IR with IR specifically defined as the distance from the center of the arterial lumen to the middle point of the media[56]; 2WTh/ED[57],[58]; 2WTh/ID[59]; WTh/ED[60]; or ID/ED[61]. Others have measured WLR from the perimeters as EP/IP[46],[47],[48], or used the area: MCSA/LCSA[14],[15],[49]; MCSA/TCSA[44]; LCSA/MCSA[43]; LCSA/TCSA[62].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, point counting has been used to estimate WLR as the average ratio of the volume density of the walls to the volume density of the lumens[15],[64]. However, many studies indicate that WLR is not constant but declines 2-10-fold in arteries of ED 20–500 μm in the human and rat kidney[56],[65]; human and rat brain[66],[67] ; a nd human and dog liver[34],[53]. Our data indicate that neither averaged WLR nor the mean values for ED, ID or WTh are applicable to even relatively small intervals of vessel caliber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, hepatic clearance of verapamil showed a dose independent pattern in hypertensive ACo rats. Although further studies are needed, profound morphological changes were previously found in hepatic vessels of rats with aortic coarctation that could affect hepatic perfusion (Novikov, Shormanov, & Kulikov, 2006;Shormanov & Kulikov, 2003).…”
Section: So Ratsmentioning
confidence: 99%